2007
DOI: 10.1111/j.1439-0396.2007.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Subacute rumen acidosis in lactating cows: an investigation in intensive Italian dairy herds

Abstract: Summary Subacute rumen acidosis (SARA) represents one of the most important metabolic disorders in intensive dairy farms that affects rumen fermentations, animal welfare, productivity and farm profitability. The aim of the present study was to study the occurrence of SARA in intensive Italian dairy herds and to determine the relationship between diet composition, ruminal pH and short chain fatty acids (SCFA) concentration. Ten commercial dairy herds were investigated; twelve cows in each herd were selected ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
1
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 14 publications
6
71
1
7
Order By: Relevance
“…Additionally, all cows tolerated the procedure as evidenced by physical behaviour responses suggesting minimal pain or discomfort. These findings are consistent with a previous study (Morgante et al 2007) where a total of 120 cows were sampled, which reported no local or general problems following the procedure. Nevertheless, some authors have reported problems related to rumenocentesis such as abscesses and peritonitis (Hollberg 1984;Aceto et al 2000;Strabel at al.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Additionally, all cows tolerated the procedure as evidenced by physical behaviour responses suggesting minimal pain or discomfort. These findings are consistent with a previous study (Morgante et al 2007) where a total of 120 cows were sampled, which reported no local or general problems following the procedure. Nevertheless, some authors have reported problems related to rumenocentesis such as abscesses and peritonitis (Hollberg 1984;Aceto et al 2000;Strabel at al.…”
Section: Discussionsupporting
confidence: 83%
“…The group of cows then had rumenocentesis (GA) performed while the control group of cows (GB) did not have rumenocentesis performed. Rumenocentesis was performed as described by Morgante et al (2007) without sedation, using a 13 ga 105 mm needle. The cow's response to rumenocentesis or sham procedure was monitored from just prior (-1 h, reference time) to 20 days following the procedure.…”
Section: Experimental Designmentioning
confidence: 99%
“…Η συγκέντρωση του βαλερικοΰ οξέος στην Μ.Κ. έχει, επίσης, συσχε τιστεί πρόσφατα με την παρουσία υποξείας δυσπε-πτικής οξέωσης (Enemark et al 2004, Bramley et al 2005, Morgante et al 2007), κάτι που αποδίδεται στην αυξημένη παραγωγή του οξέος αυτοΰ από γαλακτο-λυτικά βακτήρια, η ανάπτυξη των οποίων προϋποθέτει την ύπαρξη γαλακτικού οξέος στη ΜΚ. Επομένως, η αυξημένη συγκέντρωση βαλερικού οξέος στη μεγάλη κοιλία μπορεί να υποδεικνύει την παρουσία SARA, με προηγούμενη συγκέντρωση γαλακτικού οξέος.…”
Section: άλλες παράμετροι τον περιεχομένου της μκunclassified
“…Στο Ουισκόνσιν των ΗΠΑ διαπιστώθηκε ότι έπασχαν από υποξεια δυσπεπτική οξέωση το 19% και 26% των αγελάδων που βρίσκονταν στην αρχή και στο μέσο της γαλακτικής περιόδου, αντίστοιχα (Garrett et al 1997). Στην Ιταλία, 3 από τις 10 εκτροφές που εξετά στηκαν είχαν περισσότερες από το 33% των αγελάδων με pH ΜΚ <5,5, ενώ 5 εκτροφές είχαν περισσότερες από το 33% των αγελάδων τους με pH ΜΚ <5,8 (Morgante et al 2007). Στην Ιρλανδία, σε ομαδικό επίπεδο, SARA ανευρέθηκε σε 3 από τις 12 εκτροφές (25%) που εξετάστηκαν, ενώ άλλες 6 από τις 12 (50%) είχαν περισσότερα από το 33% των ζώων με pH ΜΚ <5,8 (O'Grady et al 2008).…”
unclassified
“…It is a common and serious health and production problem in dairy cows and herds (Nordlund 1996, Oetzel 2003. The determination of rumen pH is a key factor for the diagnosis of SARA (Morgante et al 2007, Gianesella et al 2010. Rumen pH values lower than 5.6 are considered abnormal and suggestive of either severe SARA, or possibly in combination with clinical signs, whereas rumen pH values of 5.6 to 5.8 are considered marginal and values of rumen pH higher than 5.8 are normal (Nordlund & Garrett 1994).…”
Section: Introductionmentioning
confidence: 99%